Penguatan Karakter Melalui Pendidikan Agama Islam di Era Digital - Febrianti Febrianti; Soelfema Soelfema Soelfema Soelfema; Lili Dasa Putri (Bhinneka: Jurnal Bintang Pendidikan dan Bahasa, 2025)
Increasingly complex technological advancements demand moral and intellectual improvement. In this case, education plays a crucial role in shaping a smart and noble generation. Islamic Religious Education (PAI) serves as a moral foundation as well as a source of strength that can produce a positive impact on the character building of the Indonesian generation. The study conducted can explore the role of Islamic religious education for strengthening the character of the younger generation in the midst of modern technological advances. By applying a qualitative approach, literature study method that refers to books, research journals, and scientific articles, this study concludes that personality formation through Islamic religious education values is closely related to the achievement of national education, moral values, as well as basic beliefs and local cultural values. The implementation includes teaching values, exemplary, habituation, and the application of sanctions that aim to build student character according to Islamic values.